Small Noncoding RNAs Encoded within the Bovine Herpesvirus 1 Latency-Related Gene Can Reduce Steady-State Levels of Infected Cell Protein 0 (bICP0) - Jaber, Tareq (American Society for Microbiology (ASM), 2010)
Following acute infection in mucosal epithelium, bovine herpes virus 1 (BHV-1) establishes lifelong latency in sensory neurons within trigeminal ganglia. The latency-related RNA (LR-RNA) is abundantly expressed in sensory neurons of latently infected calves. Expression of LR proteins is necessary for the latency reactivation cycle because a mutant virus that does not express LR proteins is unable to reactivate from latency after dexamethasone treatment. LR-RNA sequences also inhibit bICP0 expression, productive infection, and cell growth. However, it is unclear how LR-RNA mediates these functions. In this study, we identified a 463-bp region within the LR gene (the XbaI-PstI [XP] fragment) that inhibited bICP0 protein and RNA expression in transiently transfected mouse neuroblastoma cells. Small noncoding RNAs (sncRNAs) encoded within the XP fragment (20 to 90 nucleotides in length) were detected in transiently transfected mouse neuroblastoma cells. Two families of sncRNAs were cloned from this region, and each family was predicted to contain a mature microRNA (miRNA). Both miRNAs were predicted to base pair with bICP0 mRNA sequences, suggesting that they reduce bICP0 levels. To test this prediction, sequences encompassing the respective sncRNAs and mature miRNAs were synthesized and cloned into a small interfering RNA expression vector. Both sncRNA families and their respective miRNAs inhibited bICP0 protein expression in mouse neuroblastoma cells and productive infection in bovine cells. In trigeminal ganglia of latently infected calves, an sncRNA that migrated between nucleotides 20 and 25 hybridized to the XP fragment. During dexamethasone-induced reactivation from latency, XP-specific sncRNA levels were reduced, suggesting that these sncRNAs support the establishment and maintenance of lifelong latency in cattle.